Functional Assessment of Coronary Artery Lesions—Old and New Kids on the Block - Patel, Prashant; Rao, Ravi; Sethi, Prabhdeep; Mukherjee, Ashis; Varadarajan, Padmini; Pai, Ramdas G. (International Journal of Angiology, 2021)
Angiography is inaccurate in assessing functional significance of coronary lesions, and often stenoses deemed severe on angiographic assessment do not restrict coronary blood flow at rest or with maximal dilatation. Angiography-guided revascularization has not shown improvement in hard clinical outcomes in stable ischemic heart disease (SIHD). Most current guidelines for SIHD recommend invasive functional assessment of lesions to guide revascularization if prior evidence of ischemia is not available. There has been several recent advances and development of novel methods in this arena. Various contemporary clinical trials have been undertaken for validation of these indices. Here we review the physiological basis, tools, techniques, and evidence base for various invasive (resting as well as hyperemic) and noninvasive methods for functional assessment of coronary lesions. Left main stenosis, bifurcation lesions, serial stenosis, and acute coronary syndrome each causes unique disequilibrium that may affect measurements and require special considerations for accurate functional assessment.
Keywords: coronary stenosis; functional significance; angioplasty; coronary artery disease; perfusion